Hinch vs Canberra : behind the human headlines - Hinch, Derryn, 1944- (Melbourne University Press, 2017)
As a current affairs commentator, Derryn Hinch spent decades fighting with politicians. Then the unthinkable happened he became one. This is the inside story of Senator Hinch's first year in Canberra. Explosive, incisive, frank, brutal, and, at times, very funny.